(untitled) (Research, Society and Development, 2021)
Introduction: The Brazilian prision system has been undergoing a process of scrapping due the lack of investment and management, being the third country in the world with the largest prison population, where the growth of incarceration is not accompanied by the structural expansion of prisons in the States. The study aims to analyze sociodemographic, procedural and living conditions of individuals incarcerated in Alagoas, Brazil. Methodology: Is a cross-sectional descriptive, quantitative and retrospective study, using secondary data from InfoPen from 2015 to 2019, with the variables: age group, race/color/ethnicity, education, civil status, procedural status and prison, labor and educational activities in prisons in Alagoas, consolidated and analyzed in tables and/or graphs. Results: After analysis, a total of 8,726 thousand prisoners were found, therefore, 95.25% of People Deprived of Liberty in the state are men; for each available space there were approximately 2.5 prisoners, showing the overcrowding of the Alagoas prisons. Furthermore, it was observed that the prison system in Alagoas has a target profile of the penal system: young, black, single and with low education are the majority. The study pointed that the percentage of prisoners who perform educational activities and labor therapy was 3.9% and 9.87%, respectively, in 2019. Conclusions: Without good structural conditions and strategic actions, living and health conditions are impaired, making the need to review the structure of the prison system nationally is evident, as well as to program resocialization strategies for the prisioners.